Sodium‐Ion Batteries: Hard–Soft Carbon Composite Anodes with Synergistic Sodium Storage Performance (Adv. Funct. Mater. 24/2019). (11th June 2019) - Xie, Fei; Xu, Zhen; Jensen, Anders C. S.; Au, Heather; Lu, Yaxiang; Araullo‐Peters, Vicente; Drew, Alan J.; Hu, Yong‐Sheng; Titirici, Maria‐Magdalena
Abstract : In article number 1901072, Maria‐Magdalena Titirici and co‐workers synthesize a series of hard–soft carbon composite materials and show that at a low carbonization temperature of 1000 °C, it could show a synergistic effect due to the blockage of open pores, which suppresses solid electrolyte interface formation and increases the reversible sodium storage capacity.